Sentiment Analysis on Sharia Credit Card using Senti-Strength - Nadiyah Mu’adzah (SMART Insight, 2022)
This research was conducted to determine sentiment towards the law and the application of sharia cards issued within a period of 52 years (1970-2022). The technique involves secondary data from the metadata of 98 published publications that are in Dimensions, along with descriptive statistical analysis, meta-analysis, and sentiment analysis, then processed using Microsoft Excel 2019 and SentiStrength software. The results indicate that sharia cards have been the subject of more inquiry in the scientific literature each year. The results of the sentiment analysis show that there is a tendency for positive perceptions towards negative perceptions in the scientific literature about the existence and law of sharia cards, with a positive sentiment of 34.30% and a negative sentiment of 16.66%. However, neutral perceptions still dominate at 41.16%. The rest displayed a significant amount of positive and negative sentiment, each at 1.96%. The benefit of this research is to provide literature for the examination of sharia card law and its application while taking into account community perceptions to reduce unfavorable opinions and its flaws. By doing this, it is expected that sharia card products can attract more public interest and trust so that they can compete with conventional banking products.